Reorganising grocery shopping practices – the case of elderly consumers. Issue 4 (8th August 2022) - Hansson, Lena; Holmberg, Ulrika; Post, Anna
ABSTRACT: This paper aims to deepen the understanding of elderly consumers' grocery shopping practices during Covid-19. Drawing on the shopping-as-practice approach within social practice theory, we show how the practices unfold as the pandemic evolves and the situation of the elderly change, which implies new possibilities and limitations in grocery shopping. Qualitative telephone interviews with elderly consumers were conducted in 2020 and followed up during 2021. By analysing the elderly's grocery shopping as a social practice, we show how different modes of shopping practices (in-store, online and assisted shopping), came about, how they were reconfigured, and what made them work smoothly or not during the corona pandemic. We also show how the grocery shopping practices, and the modes involved were situated and synchronised in everyday life. The paper also discusses the implication for retailers.